DIGITAL-BASED FINANCIAL TRANSACTION RECORDING EDUCATION FOR MSMEs IN MUARA PENIMBUNG ULU VILLAGE - Patmawati, Patmawati; Meutia, Inten; Daud, Rochmawati; Khamisah, Nur; Rahmawati, Meita (LPPM Univ. Ibn Khaldun Bogor, 2025)
This service activity aims to provide an understanding of recording financial transactions for MSMEs still needs to be improved. One way that can be done to increase understanding for MSMEs in making it easier to record financial transactions is by educating them on digital-based financial transaction recording, namely the MSME business stall book application, Financial Management, Accounting – Financial Lap, MSME Business Financial Records in Muara Penimbung Ulu Village. Digital-Based For MSMEs in Muara Penimbung Ulu Village, it is known that the level of understanding of recording digital-based financial transactions is only 25%. After the service team provided material on recording digital-based financial transactions using the MSME Business Warung Book application, Financial Management, Financial Accounting-Lap, MSME Business Financial Records, it was known that the level of understanding of MSMEs has increased significantly, namely 75% from the previous only 25%. Based on the results of monitoring and evaluation of service activities, the results were obtained that MSMEs still need assistance activities for their business activities. The MSMEs stated that they were helped by this community service activity. With this service activity regarding Digital-Based Financial Transaction Recording Education for MSMEs in Muara Penimbung Ulu Village, it can help MSMEs in compiling their business financial statements.